An Agent-Based Framework for Personalized E-Learning Services - Esmahi, Larbi (International Journal of Web-Based Learning and Teaching Technologies, 2007)
This article provides an overview of personalized e-learning services and related technology and presents a multi-agent system for delivering adaptive e-learning. We discussed the main issues related to personalization in e-learning: technology advancement and the shift in perception of the learning process, one-sizefits- all vs. personalized services, and the adaptation process. The article provides also an overview of most known implemented systems for adaptive e-learning, as well as detailed description of the architecture and components of the proposed multi-agent framework. Finally, the article concludes with some comments about the dimensions to consider for implementing personalization.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9qd2x0dC4yMDA3MTAwMTAx